2023
DOI: 10.1007/s42161-023-01404-2
|View full text |Cite
|
Sign up to set email alerts
|

Coffee leaf rust (Hemileia vastatrix) is spread by rain splash from infected leaf litter in a semi-controlled experiment

Abstract: The coffee leaf rust disease (CLR), caused by the fungus Hemileia vastatrix, is an economically significant phytopathogen of cultivated Coffea species. Since coffee plants with CLR drop their infected leaves, rain splash from infected leaf litter could be one way H. vastatrix spores are dispersed, but this mechanism has not been demonstrated. Here we experimentally verify that splash from leaf litter can lead to H. vastatrix dispersal and infection. In a semi-controlled experiment, we compared the infection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As the disease advances, it impairs the plant's photosynthetic capabilities, potentially affecting its overall health and yield. Severe infections can stunt coffee plant growth, impacting both the quantity and the quality of coffee beans [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As the disease advances, it impairs the plant's photosynthetic capabilities, potentially affecting its overall health and yield. Severe infections can stunt coffee plant growth, impacting both the quantity and the quality of coffee beans [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The urediniospores may also ascend to the atmosphere and travel to other plantations (Becker and Kranz, 1977;Vandermeer and Rohani, 2014). For each of these ways of dispersal, there are agroecological management proposals to reduce the spread, like reducing the density or clustering of the plantations (Beasley et al, 2022;Ehrenbergerová et al, 2018), avoiding regular or extremely dense patterns that can make the epidemic thrive through contact or splash-mediated dispersal (Hajian-Forooshani and Vandermeer, 2021;Mora Van Cauwelaert et al, 2023a;Li et al, 2023), but also planting different trees within the plots and in the borders to reduce local and regional wind dispersal (Avelino et al, 2022;Boudrot et al, 2016;Gagliardi et al, 2020) It has been observed that workers can also disperse CLR within the plot and between regions (Becker and Kranz, 1977;Ramírez-Camejo et al, 2022;Schieber and Zentmyer, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…& Br is one of the principal coffee diseases and has caused devastating loss of production in different coffee sites around the globe (McCook and Vandermeer, 2015; Talhinhas et al, 2017). Its mechanisms for dispersal have been amply studied (Becker and Kranz, 1977; Kushalappa and Eskes, 1989; Li et al, 2023; Vandermeer et al, 2018) and thus provide a great model to explore the disease’s spatially explicit dynamics and its relations with the host’s spatial arrangement and density (Beasley et al, 2022; Gagliardi et al, 2020; Hajian-Forooshani and Vandermeer, 2021; Mora Van Cauwelaert et al, 2023a). CLR forms urediniospores that can travel to neighboring coffee plants through direct contact, water splash, or local turbulent wind conditions (Kushalappa and Eskes, 1989).…”
Section: Introductionmentioning
confidence: 99%